Mekanisme Pemotongan dan Pelaporan PPh Pasal 23 dan PPh Final pada Klien BTS Consulting - Desy Arum Putri Windarti (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Income Tax (PPh) involves various withholding and reporting mechanisms that every taxpayer needs to understand, including PPh Article 23 and Final Income Tax. Both have different characteristics, which often pose challenges in their implementation. This Final Project Report aims to understand the application of the withholding and reporting mechanisms for PPh Article 23 and Final PPh for BTS Consulting Mojokerto’s clients. Data was obtained through observation and interviews, and is supported by Law No. 7 of 2021 and Government Regulation No. 20 of 2026. Based on actual business practices, Article 23 Income Tax on vehicle rental transactions by PT MNP is withheld at a rate of 2% of the transaction payment amounting to Rp1,150,000.00, resulting in a withheld tax of Rp23,000.00. Meanwhile, the Final Income Tax for MSMEs on the consulting services utilized by PT MNP is withheld at a rate of 0.5%, in accordance with the PP 55 certificate, from the payment amount of Rp3,000,000.00, resulting in a Final Income Tax withholding of Rp15,000.00. Withholding for Article 23 Income Tax and Final Income Tax is processed through the e-Bupot Coretax application, with payments due no later than the 15th and reports due no later than the 20th of the following month. Both mechanisms have been implemented in accordance with applicable regulations through the Coretax system, with PT MNP acting as the withholding agent for both taxes.
:: Finalisasi file repositori 20 Juli 2026_Kurnadi
Keywords: Income Tax Article 23; Final Income Tax for MSMEs; Tax withholding and reporting mechanisms.